2015
DOI: 10.1002/2327-6924.12245
|View full text |Cite
|
Sign up to set email alerts
|

The Southern states: NPs made an impact in rural and healthcare shortage areas

Abstract: Purpose To investigate the distribution of nurse practitioners (NPs) in the U.S. Southern region with a focus on rural and underserved areas. Described in this study are the NP characteristics and their workforce distribution relative to rural and health professional shortage areas (HPSAs). Data sources Method: A questionnaire was administered to NPs in 12 Southern states. Other data sources included (a) the Health Resources and Services Administration, which identified HPSAs; and (b) data from the U.S. Census… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Rural NPs in particular provide a significant portion of rural healthcare services, especially, where it is difficult to recruit physicians (Kippenbrock, Buron, Odell, & Narcisse, ). A recent study confirmed that NPs are an important workforce in the primary healthcare service delivery to rural and underserved population, especially Southern U.S. states, and those NPs worked in health professional shortage areas and about half of them worked in rural areas (Kippenbrock et al., ). Their healthcare services are considered to be a substitution for primary care physicians with a positive effect on patient satisfaction and lower mortality (Kippenbrock et al., ; Martinez‐Gonzalez et al., ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Rural NPs in particular provide a significant portion of rural healthcare services, especially, where it is difficult to recruit physicians (Kippenbrock, Buron, Odell, & Narcisse, ). A recent study confirmed that NPs are an important workforce in the primary healthcare service delivery to rural and underserved population, especially Southern U.S. states, and those NPs worked in health professional shortage areas and about half of them worked in rural areas (Kippenbrock et al., ). Their healthcare services are considered to be a substitution for primary care physicians with a positive effect on patient satisfaction and lower mortality (Kippenbrock et al., ; Martinez‐Gonzalez et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…States’ regulatory environments and regulations for scope of practice differ. NPs’ ability to practice to the full extent is often limited by these regulations, reimbursement, and prescriptive authority (Kippenbrock et al., ). Currently, 24 states grant NPs authority without physician involvement in diagnosis and treatment (Gadbois, Miller, Tyler, & Intrator, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary care nurse practitioners (NPs) make up the great majority (86.5%) of the NP workforce (American Association of Nurse Practitioners [AANP], ) and are more likely to practice in rural counties and primary care shortage areas compared to primary care physicians (Buerhaus, DesRoches, Dittus, & Donelan, ). Of 1583 NPs from southern U.S. states who responded to a workforce survey, 72% practiced in shortage areas and 47% worked in rural areas (Kippenbrock, Lo, Odell, & Buron, ). Primary care NPs in rural areas are already caring for patients with mental health needs and are therefore ideal candidates for educational initiatives.…”
Section: Introductionmentioning
confidence: 99%